Ciculapod for Teaching Circulation Systems: Development and Validity of Biological Learning Media - Ristanto, Rizhal Hendi; Zahira, Safina; Rusdi, Rusdi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
The goal of this research is to develop valid and feasible Nearpod-based circulation system teaching materials. This research method uses the ADDIE development model, which includes stages of analysis, design, development, implementation, and evaluation. The research was conducted from July 2022 to June 2023. The teaching materials were tested for feasibility in material, media, and language and tested by Biology teachers and students of SMAN 14 Jakarta. The feasibility test results showed that Nearpod-based circulation system teaching materials had an average score of 3.65 (very valid) on the material aspect, 3.89 (very valid) on the media aspect, and 3.53 (very valid) on the language aspect. In Biology, the teacher trial obtained a mean value of 3.51 and an average of 3.31 for the student trials. This shows that Circulapod teaching materials are very valid and feasible to be used as learning media for circulatory systems learning in schools.